Effect of Solanum nigrum and Ricinus communis extracts on histamine and carrageenan-induced inflammation in the chicken skin - Lomash, V.; Parihar, S. K.; Jain, N. K.; Katiyar, A. K. (Cellular and Molecular Biology, 2010)
We studied anti-inflammatory effect of ethanolic extract of Solanum nigrum leaves and Ricinus communis root bark using chicken skin as model. Leaves of these plants were dried under shade and powdered. 5% Ethanol extracts were prepared using Soxhlet and injected intraperitoneally (400 mg/kg) 1 hour prior to the induction of inflammation. Inflammatory lesion were induced by intradermal injection of 0.02ml 0.05%w/v histamine (0-2 min, 15min, 30 min, 1hr and 6hr) and 1% w/v carrageenan (0-2 min, 30min, 1hr, 6hr, 12 hr and 48 hr) in different group of birds. Increase in vascular permeability was studied using Evans blue as a permeability marker both qualitatively and quantitatively. Cellular events were studied in skin lesions at various time intervals and cells were counted at high power objective under microscope. Both, extracts exhibited significant decrease in permeability response at an early stage (0-2min) of histamine as well as in carrageenan induced inflammatory lesions. There was a significant (p< 0.05) suppression in the emigration of heterophils, monocytoid cells, basophils and total leukocytosis in Solanum nigrum and Ricinus communis pretreated chicken skin lesions as compared to the control. The present study suggested antihistamine and anti-inflammatory properties of ethnolic extract of Solanum nigrum and Ricinus communis.